Quality evaluation of compounds in leaves of six Taxus species based on UPLC-MS/MS and chemometrics - Cai, Qingzhu; Song, Qiang; Jiang, Kunxia; Lin, Yao; Zhang, Ying; Zhang, Jirong; Lin, Shuqing; Huang, Lina; Xue, Qihuang; Huang, Zehao; Xu, Wen; Xu, Wei; et al. (Frontiers in Chemistry, 2023)
Taxus species are used as medicinal plants all over the world. The leaves of Taxus species are a sustainable medicinal resource rich in taxoids and flavonoids. When leaves are used as raw medicinal materials, traditional identification methods cannot effectively identify Taxus species, because their appearance and morphological characteristics are almost the same, and the probability of error identification will increase based on the subjective consciousness of the experimenter. Moreover, the leaves of different Taxus species have been widely used, but their chemical components are similar and lacking systematic comparative research, which is challenging for quality assessment. In this study, ultra-high-performance liquid chromatography coupled with triple quadrupole mass spectrometry was established for the simultaneous determination of eight taxoids, four flavanols, five flavonols, two dihydroflavones, and five biflavones in the leaves of six Taxus species (T. mairei, T. chinensis, T. yunnanensis, T. wallichiana, T. cuspidata, and T. media.) and combined with chemometric. The feasibility of this method in distinguishing six different Taxus species was evaluated. Chemometrics including hierarchical cluster analysis, principal component analysis, orthogonal partial least squares-discriminate analysis, random forest iterative modeling, and fisher linear discriminant analysis were used to differentiate and evaluate the six Taxus species. In conclusion, this study established a method for the simultaneous determination of 24 analytes in the leaves of six Taxus species, revealing the differences in the chemical components of the different species. Six compounds, namely, 7-xylosyl-10-deacetyltaxol, ginkgetin, rutin, aromadendrin, 10-deacetyl baccatin III, and epigallocatechin, were obtained through chemometrics for the first time, which can be used as important chemical markers to quickly distinguish six Taxus species.